Survival and toxicity in patients with human papilloma virus‐associated oropharyngeal squamous cell cancer receiving trimodality therapy including transoral robotic surgery. Issue 10 (25th June 2021) - Sun, Lova; Shimunov, David; Tan, Erik X.; Swisher‐Mcclure, Samuel; Lin, Alexander; Lukens, John N.; Basu, Devraj; Chalian, Ara A.; Cannady, Steven B.; Newman, Jason G.; Rajasekaran, Karthik; O'Malley, Bert W.; et al.
Abstract: Background: Patients with oropharyngeal cancer who undergo transoral robotic surgery (TORS) and have high‐risk features generally receive adjuvant chemoradiotherapy or trimodality therapy (TMT). The notion that TMT leads to high toxicity is largely based on studies that included human papilloma virus (HPV)‐negative cancers and/or nonrobotic surgery; we sought to describe outcomes in HPV‐associated oropharyngeal squamous cell cancer (HPV + OPSCC) undergoing TORS‐TMT. Methods: In consecutive patients with HPV + OPSCC receiving TMT at an academic center from 2010 to 2017, survival was estimated using Kaplan–Meier methodology, and toxicities were ascertained via chart review. Results: In our cohort of 178 patients, 5‐year survival was 93.6%. Feeding tube rates were 25.8% at therapy completion and 0.7% at 1 year. Rates of grade ≥ 3 kidney injury, anemia, and neutropenia in cisplatin‐treated patients were 2.7%, 3.4%, and 11.0%, respectively. Conclusions: Patients with HPV + OPSCC who underwent TORS‐TMT had excellent survival and low rates of toxicity and feeding tube dependence. These outcomes compare favorably to historical cohorts treated with definitive chemoradiotherapy.